Economic analysis of soyabean marketing in logo local government area of Benue state, Nigeria - Adu, V.M (ADAN JOURNAL OF AGRICULTURE, 2026)
This study examined the economic analysis of soyabean marketing in Logo Local Government Area of Benue State. Specifically, the study sought to: determine the socio- economic characteristics of soyabeans marketers in the study area, Profitability of soyabean marketing and describe the constraints of soyabeans marketing. Despite the increasing demand and profitability associated with soybean marketing, marketers in Logo Local Government Area still face challenges such as unequal market share distribution, inadequate modern marketing practices, and limited access to improved technologies. These challenges affect efficiency, profitability, and the overall performance of soybean marketing, thereby necessitating the need for this study. The population for this study includes two hundred and forty-one (241) registered soyabean marketers in Logo Local Government Area of Benue State, Nigeria. The sample size was obtained using Taro-Yamane (1967) with total number of one hundred and fifty (150). The model specification used in this work was descriptive statistics, gross margin analysis and factors analysis model. Table one showed that majority (73.3%) of the soyabean marketers were males while 26.7% were females. This showed that men involved in soyabean marketing more than women in the study area. Table 1 shows that majority (73.3%) of the soyabean marketers were males while 26.7% were females. This showed that men were involved in soyabean marketing activities more than women in the study area. Table 2 showed that the result of costs marketing soyabean incurred a total mean of 67285.00 the returns of marketing soyabean incurred a total mean of 72639.17. It revealed a mean gross margin of 5354.17. The returns on investments (ROI) showed that for every N1 invested in marketing of soyabean, a return of 08k is realize. Table 3 showed the constraints were named based on the item loadings. Factor 1, 2 and 3 respectively. Factors which were highly loaded under factor 1 include Perishability of soyabean (0.468), Low demand for produce (1.356), Inadequate credit facility (0.716), and Inadequate Road network (0.728). Factor 2 which include Lack of storage facility (0.811), Inadequate distribution system (0.808), High cost of transportation (0.93), High rate of taxation (1.169) and Lack of market information (0.673). Factor 3 which include Price fluctuations (0.732) and Poor accessibility to markets (0.865). In conclusion, there is a moderate level of inequality in the distribution of market shares among soybean marketers in Logo Local Government Area of Benue State. This calls for a strategic and inclusive approach to address disparities, fostering fair competition and opportunities for smaller participants in the soybean market. Based on the findings of this study, the following are recommended: Farmers should be encouraged to adopt modern agricultural technologies and practices to enhance the efficiency of soybean production. This could include providing training programs on sustainable farming methods, the use of advanced machinery, and precision agricultural techniques. By embracing technology, farmers can improve yields, reduce production costs, and contribute to the overall performance of the soybean market.